A pozsonyi magyar királyi Erzsébet Tudományegyetem Pécsre költözése és harca a fennmaradásért a II. világháborúig: THE RELOCATION OF THE HUNGARIAN ROYAL ELIZABETH UNIVERSITY OF BRATISLAVA TO PÉCS, AND ITS FIGHT FOR SURVIVAL UNTIL WORLD WAR II - Duczon, Árpád (Közép-Európai Közlemények, 2019)
Angol: The predecessor of the University of Pécs is the Elisabeth University, founded in 1912, which, however, suspended its operation after the Czech occupation of the city after World War I. In accordance with Act XXV of 1921, the National Assembly had the University move to Pécs temporarily, however, this procedure could only take place slowly due to the Serbian occupation, and the first academic year did not start until the autumn of 1923. However, the integration of the new university into the life of the city of Pécs encountered various difficulties. For example, the situation in the city seemed hopeless after the war and the Serbian occupation; campuses had to be established through church and city donations. In addition to the difficulties of integration, the University had to find its own image and organize a scientific dialogue of its own right. Accordingly, scientific journals issued by the institution had to be established. The first such paper, Minerva, was finally published in the twenties, which was linked to the name of Tivadar Thienemann and the Faculty of Humanities. This was followed by Pannónia, associated to Jenő Koltay-Kastner in the 1930s, which in the first volumes also focused on humanities. The youth organization that started immediately after the relocation also played a part in the integration of the University into urban life and other universities. This organization started as early as in the transitional period of Budapest, and then kept on developing in Pécs. Later in the 1930s, the university students became significantly radicalized. This study first describes the history of the University by reviewing the latest literature published thanks to the 650th anniversary of the history of the University of Pécs as well as how the relocation of Elisabeth University to Pécs took place. After that, relying on press sources, the paper gains insight into how the University took root between the two world wars at the site where it is currently operating. Magyar A Pécsi Tudományegyetem elődje, az Erzsébet Tudományegyetem 1912-ben jött létre, azonban az első világháború utáni csehszlovák megszállás után beszüntette tevékenységét. A nemzetgyűlés az 1921. évi XXV. törvénycikkel ideiglenesen Pécsre helyezte az intézményt, azonban a szerb megszállás miatt csak 1923 őszén indulhatott meg itt a képzés. Az új egyetem csak nehezen illeszkedett bele a város kulturális-tudományos életébe. Éppen ezért saját tudományos folyóiratokat kellett létrehozniuk, hogy eredményeiket publikálhassák. Az első ilyen volt a Minerva, amit Thienemann Tivadar és a Bölcsészettudományi adott ki. Ezt követte a Pannónia című lap, amit Koltay-Kastner Jenőhöz kötnek az 1930-as években. A diákszervezetek létrehozása szintén fontos szegmense volt az egyetemi beilleszkedésének. Az 1930-as évek végére az egyetemi hallgatók többsége radikális véleményt fogalmazott meg a politikai rendszerrel és a háborúval kapcsolatban. A tanulmány célja, hogy bemutassa az egyetem beilleszkedésének történetét szakirodalmakra és forrásokra támaszkodva. Az áthelyezés és az „új egyetem” alapításának 650 éves évfordulója kapcsán érdemes lehet visszatekintenünk az eddigi útra, az akkori nehézségekre és problémákra-